Using machine learning to predict patient-reported symptom clusters in prostate cancer patients receiving radiotherapy - Rammant, Elke; Deman, Emile; Fonteyne, Valérie; Poppe, Lindsay; Bultijnck, Renée; Dirix, Piet; De Meerleer, Gert; Haustermans, Karin; Van Hecke, Ann; Aguado-Barrera, Miguel E.; Avuzzi, Barbara; Azria, David; et al. (Health and quality of life outcomes, 2026)
Prostate cancer (PC) survivors frequently experience multiple co-occurring symptoms that adversely affect health-related quality of life (HRQoL). Identifying symptom clusters (SCs) may help to improve symptom management and patient care. The aim of this study is to investigate (1) SCs in PC patients, (2) associations of SCs with HRQoL, and (3) predictors of SCs.